2015
DOI: 10.1007/s10803-015-2461-2
|View full text |Cite
|
Sign up to set email alerts
|

Failure in Pantomime Action Execution Correlates with the Severity of Social Behavior Deficits in Children with Autism: A Praxis Study

Abstract: Here we describe the performance of children with autism, their siblings, and typically developing children using the Florida Apraxia Battery. Children with autism showed the lowest performance in all sections of the test. They were mostly impaired in pantomime actions execution on imitation and on verbal command, and in imitation of meaningless gestures. Interestingly, a correlation was found between performance in pantomime actions and the severity of social behavior deficits. We conclude that the presence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
33
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 33 publications
3
33
0
Order By: Relevance
“…Despite the reasonable conjecture that such errors could be the result of an imitation difference, motor issues cannot be excluded as a possible cause of palm orientation errors. From 50 to 80% of children with ASD exhibit motor impairments [15][16][17][18], including basic motor skill deficits in reaching and walking [19,20], gross and fine motor incoordination [15,17,21], as well as deficits in praxis/motor planning [22][23][24][25][26], and such deficits have been found to extend to deaf, signing children with ASD [27]. Children with motor issues with the articulation of signs might execute signs with the palm facing the midline of the body, which is the default resting position of the palm when the arms are hanging at one's sides.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the reasonable conjecture that such errors could be the result of an imitation difference, motor issues cannot be excluded as a possible cause of palm orientation errors. From 50 to 80% of children with ASD exhibit motor impairments [15][16][17][18], including basic motor skill deficits in reaching and walking [19,20], gross and fine motor incoordination [15,17,21], as well as deficits in praxis/motor planning [22][23][24][25][26], and such deficits have been found to extend to deaf, signing children with ASD [27]. Children with motor issues with the articulation of signs might execute signs with the palm facing the midline of the body, which is the default resting position of the palm when the arms are hanging at one's sides.…”
Section: Introductionmentioning
confidence: 99%
“…The two major functional roles attributed to pantomime during everyday social interactions are gestural depiction during interpersonal communication (Clark, 1996) and demonstration during supervised learning (Gärdenfors, 2017). However, pantomime has a diverse profile of social uses (Zywiczynski et al, 2018) that spans from the performing art of mime theater (Hall, 2009) through to the neuropsychological testing that is done to diagnose syndromes, such as apraxia (Heilman et al, 1982;Hoeren et al, 2014), aphasia (Rose et al, 2017;van Nispen et al, 2018), and autism (Rogers et al, 1996;Smith and Bryson, 2007;Gizzonio et al, 2015).…”
Section: What Pantomime Is and Is Notmentioning
confidence: 99%
“…In his seminal paper, he reported that infants with the disorder were unable to make anticipatory motor adjustments, e.g., they failed “ to assume at any time an anticipatory posture preparatory for being picked up” (Kanner, 1943, p. 242). Subsequent investigations confirmed that persons with ASD exhibit impairments in the motor domain; some scholars have even suggested that such impairments might represent a core component of autism (e.g., De Meyer et al., 1972; Jones and Prior, 1985; Rogers et al., 1996; Smith and Bryson, 2007; Cossu et al., 2012; Gizzonio et al., 2015; Bo et al., 2016).…”
Section: Introductionmentioning
confidence: 97%